Structural and functional basis of mammalian microRNA biogenesis by Dicer - Zapletal, David; Taborska, Eliska; Pasulka, Josef; Malik, Radek; Kubicek, Karel; Zanova, Martina; Much, Christian; Sebesta, Marek; Buccheri, Valeria; Horvat, Filip; Jenickova, Irena; Prochazkova, Michaela; et al. (Molecular cell, 2022)
MicroRNA (miRNA) and RNA interference (RNAi) pathways rely on small RNAs produced by Dicer endonucleases. Mammalian Dicer primarily supports the essential gene-regulating miRNA pathway, but how it is specifically adapted to miRNA biogenesis is unknown. We show that the adaptation entails a unique structural role of Dicer's DExD/H helicase domain. Although mice tolerate loss of its putative ATPase function, the complete absence of the domain is lethal because it assures high-fidelity miRNA biogenesis. Structures of murine Dicer•-miRNA precursor complexes revealed that the DExD/H domain has a helicase-unrelated structural function. It locks Dicer in a closed state, which facilitates miRNA precursor selection. Transition to a cleavage-competent open state is stimulated by Dicer-binding protein TARBP2. Absence of the DExD/H domain or its mutations unlocks the closed state, reduces substrate selectivity, and activates RNAi. Thus, the DExD/H domain structurally contributes to mammalian miRNA biogenesis and underlies mechanistical partitioning of miRNA and RNAi pathways.
Keywords: savci; RNAi; mirtron; miRNA; MicroRNAs; cryo-EM; dsRNA; helicase; zvířata; Mammals; myši; dsRBD; PKR; Mice; transportní proteiny; Carrier Proteins; Ribonuclease III; RNA Interference; mikro RNA; Animals; DExD; RNA interference; TARBP2; Dicer; ribonukleasa III